Perbandingan Sistem Swakelola Oleh Masyarakat Dan Sistem Kontrak Pada Penanganan Pekerjaan Prasarana Bangunan Komunal Pada Permukiman Di Kota Batu - Oktovyanti, Nunky (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2014)
Completion of infrastructure development on the community in Batu done with the system and of self-managed by the community contractual system. Objects arranged in a communal building includes communal WWTP, neighborhood street paving and drainage environment. The purpose of this study was: (1) Knowing the comparison of project implementation stages of construction between self-managed system with the implementation of the contract system of employment that are Communal Settlement Infrastructure (Communal WWTP, Paving Roads and Drainage Environment) in Batu. (2) Knowing the comparison, the pattern of handling residential infrastructure development work on the community (Communal WWTP, neighborhood street paving and drainage environment) between the self-management system and contract system by determining the weights of criteria among a number of alternatives using AHP method. (3) Choosing a treatment pattern based on a quantitative analysis of the implementation of the infrastructure work on the community building with self-management system and contract system in Batu.This research was conducted through a questionnaire survey methodas well as interviews with several stakeholders, field supervisors, facilitatorsElectricfield(TFL), contractors, self-help groups (SHG), andcommunityself-relianceAgency(BKM) in Batu, Java east. Consists of 17 questionnaire swere distributed and research uses the Analytic Hierarchy Process Method (AHP). The criteria used in the comparison of self-management system and contract system is the human resources,funding, quality, time, operation and maintenance.The analysis showed that the funds criteria is the criteria with weight value/highest priority(40.4%), and Human Resource(19.4%), quality o fproject implementation(18.6%),operations and maintenance(10.6%),time of execution of the project(11.1%). Alternative implementation of the project for infrastructure work constraction communal settlement in Batu is the most preferredis self-managed systems with weights(52%), while the total contract system(48%) of the results of the evaluation of each alternative.Â